Hypofractionated Whole-Breast Irradiation Focus on Coronary Arteries and Cardiac Toxicity—A Narrative Review - Mireştean, Camil Ciprian; Iancu, Roxana Irina; Iancu, Dragoş Petru Teodor (Frontiers in Oncology, 2022)
Breast cancer is the most common cancer among women worldwide, often treated with radiotherapy. Whole breast irradiation (WBI) is one of the most common types of irradiation. Hypo-fractionated whole breast irradiation (HF-WBI) reduces from 5 weeks to 3 weeks the treatment time. Recent radiobiological and clinical evidences recommends the use of HF-WBI regardless of the age or stage of disease, and is proved that hypo-fractionation is non- inferior to conventional fractionation regimen irradiation. However, some studies report an increased incidence of heart related deaths in the case of breast irradiation by hypo-fractionation especially in patients with pre-existing cardiac risk factors at the time of treatment. Due to the new technical possibilities of radiotherapy techniques, HF-WBI can reduce the risk of cardiac toxicity by controlling the doses received both by the heart and by the anatomical structures of the heart. The radiobiological "double trouble"in particular "treble trouble" for hypo-fractionated regimenscan be avoided by improving the methods of heart sparing, based on guided imaging irradiation (IGRT) and by using respiration control techniques so that late cardiac toxicity is expected to be limited. However, long-term follow up of patients treated with HF-WBI with modern radiotherapy techniques is necessary considering the progress of systemic therapy with prolonged survival, but also the cardiac toxicity of new oncological treatments. The still unknown effects of small doses spread in large volumes on lung tissue may increase the risk of second malignancy but they can also be indirectly involved in the development of a late heart disease. It is also necessary to develop multivariable radiobiological models that include histological, molecular, clinical and therapeutic parameters to identify risk groups and dosimetric tolerance in order to limit the incidence of late cardiac events.